Antioxidant and antimicrobial properties of carbohydrate-based films enriched with cinnamon essential oil by Pickering emulsion method. (March 2019) - Fasihi, Hadi; Noshirvani, Nooshin; Hashemi, Mahdi; Fazilati, Mohammad; Salavati, Hossein; Coma, Véronique
Graphical abstract: Highlights: CMC-PVA- CEO active films were produced from Pickering filmogenic emulsions. Morphological, optical, antioxidant and antifungal properties of films were examined. The active films exhibited superior antifungal properties in vitro and in bread slices. The active films showed good antioxidant activity. The films stabilized by Pickering emulsion method have good potential to preserve bread. Abstract: The overall aim of this research is to introduce a novel approach for maintaining a greater amount of cinnamon essential oil (CEO) in the material. We used the Pickering stabilization method, in order to increase the antioxidant and antifungal properties of carboxymethyl cellulose (CMC)-polyvinyl alcohol (PVA) based films. The light transmission, antioxidant and antifungal properties of the films were studied. In addition, the effect of the packaging was studied on the shelf life of bread. The results showed great improvement of the antifungal and antioxidant properties of the prepared films. The films containing 1.5 and 3% CEO were highly effective against P. digitatum and showed complete inhibition in in vitro and in vivo tests. Moreover, the films exhibited a good UV inhibitory effect. Consequently, the CEO Pickering emulsion was an ideal alternative for incorporation with CMC-PVA based films for increasing the shelf life of bread.